Die Fabrikation von Kreativität Organisation und Kommunikation in der Mode - Nyfeler, Judith (Sozialtheorie, 2019)
How is creativity created in fashion? Judith Nyfeler examines the actors involved along with their specific organizational methods (routines, technologies, projects, cooperations) and linguistic expressions (narratives, shows, storytelling). It turns out that instead of constantly renewing, variants are formed, whereby the formal facade of creativity and the operative activities of production are organizationally resolved from each other. The formation of variants is enhanced by language elements, which are always worked on, which in turn represents the basis for change as well as stability in fashion.